Relational dialogue in emotion‐focused therapy. Issue 2 (15th October 2020) - Elliott, Robert; Macdonald, James
Abstract: Objectives: In emotion‐focused therapy (EFT) relational processes between the therapist and client are not normally an explicit focus unless the therapist and client encounter difficulties that interfere with therapeutic work. When this does happen, however, relational dialogue (including meta‐communication) becomes necessary. We present the principles and stages of the EFT task Relational Dialogue for Alliance Difficulties . Methods and Results: After describing this little‐known task, we illustrate its application in the successful treatment of a severely socially anxious female client with complex trauma and emotional fragility. Using transcripts and detailed descriptions we highlight the alliance difficulty marker subtype, relational dialogue principles and the stages of EFT alliance difficulty work.